Peran Kepolisian dalam Penegakan Hukum Tindak Pidana Penyelundupan Impor Pakaian Bekas di Kepolisian Daerah Sumatera Utara - Tri Nova Eka Putri Sinamo; Rizkan Zulyadi; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to examine and analyze the rule of law, the role of the police in law enforcement and the obstacles faced by the police in law enforcement of the criminal act of smuggling used clothing imports in the North Sumatra Region. The research method used is the normative juridical method and the nature of the descriptive analysis of the analyst. The results of the study indicate that the legal rules regarding the criminal act of importing used clothing are regulated in Law no. 7 of 2014 concerning Trade, Law no. 17 of 2006 concerning amendments to the Customs Law, and Regulation of the Minister of Trade No.51/M-DAG/PER/7/2015 concerning the Prohibition of the Import of Used Clothing. The role of the Police is that the North Sumatran Police cooperate with customs officials and examine documents or completeness of permits for the movement of goods, in this case used clothes from abroad, which will be delivered to the city of Padang via Tanjung Balai waters. The obstacle faced in law enforcement is where the North Sumatra Police personnel are negligent in carrying out their duties. The North Sumatra Police's facilities and infrastructure have no obstacles, because the facilities and infrastructure are complete, the community factor where many people still don't report to law enforcement officials regarding the entry of used clothes into Indonesia, especially North Sumatra and cultural factors where people feel comfortable selling used clothes.